The structure of Marx's world-view - McMurtry, John (Princeton University Press, 1978)
This book sets forth a clear and systematic approach to Marx's thought that finally makes possible a coherent interpretation of all of his published works. Although Marx's philosophy is usually regarded as one of the most influential ever written, its seeming ambiguities and contradictions have long puzzled readers. By uncovering the framework that unifies the writings of Karl Marx, John McMurtry has made an advance of signal importance for all areas of Marxian studies